2021
DOI: 10.1007/s42452-020-04039-5
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategies for small-scale rearing black soldier fly larvae (Hermetia illucens) as organic waste recycler

Abstract: Processing organic waste using black soldier fly (BSF)-based technology offers a promising alternative for sustainable organic waste management and urban sanitation. This study was conducted to assess the influence of feeding strategies on the efficacy of BSF larvae to recycle organic wastes into value products. Fruit waste and chicken manure were used as organic waste samples while commercial chicken feed was used as a control, and were processed for 15 days in circular plastic containers (Ø 30 × 12 cm) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
0
14
2
Order By: Relevance
“…Surprisingly, our results showed that the development time of larvae was not different among the groups. This result is in contrast with other researches [ 7 , 8 , 29 ]. It is not easy to explain this point, thus further insights need to clarify it, evaluating the metabolic profile of larvae in detail.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, our results showed that the development time of larvae was not different among the groups. This result is in contrast with other researches [ 7 , 8 , 29 ]. It is not easy to explain this point, thus further insights need to clarify it, evaluating the metabolic profile of larvae in detail.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, considering the protein and moisture percentages of each substrate, the total protein available for larvae growth were: 679.6, 279.8, 543.1, and 482.4 g for control, V100, V50 + B50, and V75 + B25 groups, respectively. Even if the moisture percentage in each substrate were within the suitable range for BSF indicated by Cammack and Tomberlin [ 28 ], Dzepe et al [ 29 ], testing five substrates with increasing moisture content from 40 to 80%, observed that increasing the substrate moisture content reduces the larval feed reduction, wet weight, development time, body size, and body thickness. Lalander et al [ 30 ] also reported that high levels of moisture in the substrate reduced the biomass conversion ratio and survival rate of the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Highest larval growth rate (13.4 mg/d) was found in larvae reared on SW and was higher than in larvae reared on the reference substrate CF (7.2 mg/d) and PMLCF (7.3 mg/d). The final larval weight (69 mg) on the reference substrate was in the range of larval weights obtained on a chicken feed in another experiment [ 13 ]. Larval growth rate (13.4 mg/d) of larvae fed SW containing pasta, potatoes and vegetables in the experiment was higher than the VEGFRU or FRU substrates [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chicken feed (Agruniek Rijnvallei Voer BV, Wageningen, The Netherlands) was used as a reference diet (19.8% crude protein, 5.3% fat, 6.2% crude fiber, and 5.2% crude ash). Chicken feed was also used as a reference diet in other experiments [ 12 , 13 ]. Pig manure solid were sow faeces provided by Van Beek SPF Varkens B.V. (Lelystad, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Larvae are fed with household wastes, agroindustrial wastes or to a lesser extent with animal or marine waste. They are then harvested and processed as live or dehydrated larvae, larval meal and/or fat [ 75 ]. The meal and fat are used as ingredients in the formulation of food (dry and wet) and treats for dogs and cats, while the live or dehydrated larvae are offered as a dietary supplement for exotic pets.…”
Section: Current Use Of Insects As Food Ingredients For Dogs Cats And...mentioning
confidence: 99%